Green Chemistry: Sustainable Future to Science and Technology: Exploring the Applications and Impact of Green Chemistry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Green chemistry for chemical synthesis addresses our future challenges in working with chemical processes and products by inventing novel reactions that can maximize the desired products and minimize by seeking greener solvents and environmentally benign. The emerging area of Green chemistry is a need in the design and attainment of sustainable development. Green chemistry is the utilization of a set of principles that will help reduce the use and generation of hazardous substances during the manufacture and application of chemical products. In this review, a brief some industrial applications are discussed.